Language Acquisition of A Bilingual Child Indonesian English - Lutfi Eksawati; Hidayat Nur Septiadi; Rina Dwi Novari (Universitas Sebelas Maret, 2022)
This research aims to examine syntactic development in children, especially in mastering sentences formed by children. The approach used is qualitative with a case study method, through systematic observation of language acquisition in Indonesian-English bilingual children. This research relies on the understanding that the syntactic development of bilingual children has unique characteristics, including the potential for transfer between languages that can influence sentence use patterns. The main focus is to identify the stages of syntactic development, from single-word utterances to complex sentences, as well as comparing the dynamics of first language (L1) and second language (L2) acquisition. The main data source in this research is a child named Mayesa Hafsah Kirana (MHK), the first daughter of the couple Retno Hening and Tatang, who studied the first and second languages simultaneously in a bilingual environment. This child grew up in a family environment that supported the consistent use of Indonesian and English, which allowed this research to explore the process of language acquisition in depth. Apart from that, the selection of subjects also takes into account the socio-cultural background that enriches the research context. Data was collected using three main instruments, namely notebooks, video recordings of Kirana telling stories, and interview results. Data collection methods include observation, interviews, and documentation. To analyze the data, researchers translated the words spoken into Indonesian with the help of a dictionary, especially for utterances that were ambiguous or unclear. The analysis technique used is an interactive analysis model. The results of the research show that the development of MHK language syntax in Indonesian and English is balanced, with transfer in the process of syntactic development.